A 15-Year Review of Clinical Practice Patterns and Evidence-Based Medicine in Carpometacarpal Joint Arthroplasty. (March 2023) - Shah, Nikhil D.; Yuksel, Selcen; Sasson, Daniel C.; Kearney, Aaron M.; Neumeister, Michael W.; Gosain, Arun K.
Background: The purpose of this study was to help understand national practice patterns in carpometacarpal (CMC) arthroplasty and how they have evolved with evidence-based recommendations over the past 15 years. Methods: The American Board of Plastic Surgery (ABPS) started collecting practice data on primary CMC joint arthroplasty in 2006 as a portion of its continuous certification (CC) process. Data on primary CMC arthroplasty from May 2006 through December 2013 were reviewed and compared to those from January 2014 to March 2020. National practice trends observed in these data were evaluated. Comprehensive evidence-based medicine reviews published in 2008, 2011, 2013, and 2017 were reviewed alongside the CC data. Results: In all, 570 primary CMC joint arthroplasty cases were included from May 2006 to March 2020. The average age at the time of repair was 62 years and the patient population was predominantly female (79%). Most cases were done under general anesthesia (69%), and there was an increase in the use of regional anesthesia with nerve block when our 2 cohorts were compared (27% vs 37%; P = .020). A trapezium excision with flexor carpi radialis tendon ligament reconstruction was the most popular technique (72%) and an increase in the use of simple trapeziectomy was observed (6% vs 14%; P = .001). One-third of patients did not receive any form of deep vein thrombosis prophylaxis. Conclusions: The ABPS CC data provide a databank that allows for direct observation of national practice trends and sheds light on potential avenues for improvement in patient care.